2015
DOI: 10.1007/s00438-015-1125-4
|View full text |Cite
|
Sign up to set email alerts
|

Selection of reference genes for analysis of stress-responsive genes after challenge with viruses and temperature changes in the silkworm Bombyx mori

Abstract: Viruses and high temperature (HT) are the primary threats to silkworms. Changes in the expression of stress-response genes can be measured using quantitative polymerase chain reaction (qPCR) after exposure to viruses or HT. However, appropriate reference genes (RGs) for qPCR data normalization have not been established in this organism. In this study, we summarized the RGs used in the previous silkworm studies after infection with Bombyx mori nucleopolyhedrovirus (BmNPV), B. mori cytoplasmic polyhedrosis virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 26 publications
0
35
0
1
Order By: Relevance
“…It was reported that the expression of reference genes is not static in different species, tissues or experimental conditions (Lu et al, 2013 ), so the stability verifications of reference genes are necessary before evaluating target gene expression levels by RT-qPCR. Recently, more and more research considered this and the stability verifications were also performed in many Lepidoptera insects, for example: Plutella xylostella (Fu et al, 2013 ), Danaus plexippus (Pan et al, 2015 ), Sesamia inferens (Lu et al, 2015 ), Heliconius numata (Piron Prunier et al, 2016 ), Thitarodes armoricanus (Liu et al, 2016 ), Bombyx mori (Guo et al, 2016 ), Helicoverpa armigera (Chandra et al, 2017 ), Grapholita molesta (Wang et al, 2017 ), Chilo suppressalis (Xu et al, 2017 ), Spodoptera exigua (Płachetka-Bozek and Augustyniak, 2017 ), and grassland caterpillars (Zhang et al, 2017 ). As the important agricultural pest, the identification and validation of reference genes in S. litura with three biotic factors and four abiotic treatments were also investigated (Lu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the expression of reference genes is not static in different species, tissues or experimental conditions (Lu et al, 2013 ), so the stability verifications of reference genes are necessary before evaluating target gene expression levels by RT-qPCR. Recently, more and more research considered this and the stability verifications were also performed in many Lepidoptera insects, for example: Plutella xylostella (Fu et al, 2013 ), Danaus plexippus (Pan et al, 2015 ), Sesamia inferens (Lu et al, 2015 ), Heliconius numata (Piron Prunier et al, 2016 ), Thitarodes armoricanus (Liu et al, 2016 ), Bombyx mori (Guo et al, 2016 ), Helicoverpa armigera (Chandra et al, 2017 ), Grapholita molesta (Wang et al, 2017 ), Chilo suppressalis (Xu et al, 2017 ), Spodoptera exigua (Płachetka-Bozek and Augustyniak, 2017 ), and grassland caterpillars (Zhang et al, 2017 ). As the important agricultural pest, the identification and validation of reference genes in S. litura with three biotic factors and four abiotic treatments were also investigated (Lu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…As determined by RefFinder ( Figure 3 ), tif was a relatively stable reference gene under all of our experimental conditions. Actually, tif have been widely used as housekeeping genes for gene expression analysis during Bombyx mori Cytoplasmic Polyhedrosis Virus (BmCPV) and Bombyx mori Bidensovirus (BmBDV) infection ( Guo et al, 2016 ). Ache 2 was the most stable reference gene under IAPV infection, while β -actin was the most stable reference gene under CBPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Diapause of most insects was mainly affected by photoperiod and temperature. In past studies, the screening of reference genes of Drosophila melanogaster ( Ponton et al 2011 ), Leptinotarsa decemlineata ( Shi et al 2013 ), Helicoverpa armigera ( Zhang et al 2015 ), Bombyx mori ( Guo et al 2016 ), and Harmonia axyridis ( Qu et al 2018 ) under main environmental factors was completed by GeNorm, NormFinder, Bestkeeper, and ∆CT method. In this study, the expression profiles of 10 candidate reference genes of C. nipponensis were analyzed under different conditions by the same four statistical algorithms, GeNorm ( Vandesompele et al 2002 ), NormFinder ( Andersen et al 2004 ), Bestkeeper ( Pfaffl 2004 ), and ∆CT method ( Silver et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%